1988
DOI: 10.1016/0014-5793(88)80558-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an intronless human calmodulin‐like pseudogene

Abstract: We report the isolation and characterization of a human genomic clone encoding a calmodulin-like psbudogene. It contains an open reading frame of 444 nucleotides, not interrupted by introns. The nucleotide sequence of the open reading frame shows 80%, 71% and 69% identity to the previously reported human calmodulin cDNAs kht6 [17], hCWP [22], and lhCE1 [23], respectively. The derived amino acid sequence has only 85% identity to vertebrate calmodulin, but shows four potentially functional Caz+-binding loops. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Considering that the three calmodulin genes in humans diverge as much as is theoretically possible, while still encoding identical proteins (17), it is clear that the entire protein is stringently conserved to preserve proper function. The sequence of the NB-1 transcript is identical to that of a previously reported intronless calmodulin-like gene originally described as an unexpressed pseudogene (25). Although genomic sequences specifying calmodulin-like coding sequences that differ by more than three amino acids from the authentic protein have also been described in other vertebrates (26,27), the NB-1 gene is the only one to our knowledge that has been shown to be expressed at the mRNA level.…”
mentioning
confidence: 49%
“…Considering that the three calmodulin genes in humans diverge as much as is theoretically possible, while still encoding identical proteins (17), it is clear that the entire protein is stringently conserved to preserve proper function. The sequence of the NB-1 transcript is identical to that of a previously reported intronless calmodulin-like gene originally described as an unexpressed pseudogene (25). Although genomic sequences specifying calmodulin-like coding sequences that differ by more than three amino acids from the authentic protein have also been described in other vertebrates (26,27), the NB-1 gene is the only one to our knowledge that has been shown to be expressed at the mRNA level.…”
mentioning
confidence: 49%
“…This finding has introduced the unusual concept of multiple genes -one protein, and has raised interesting questions concerning the evolution and functional significance of the CALM gene family. In subsequent work, the Strehler group has characterized all three human CALM genes [24,25] (before the advent of the human genome sequence), and in the process, has discovered multiple CALM pseudogenes [26] , as well as an intriguing intronless calmodulin-like gene [27] (see below). Dr. Strehler's group also has provided the first analysis of all three CALM gene promoters and a direct comparison of their relative transcriptional strengths [25] .…”
Section: Alternative Splicing Controls the Membrane Targeting Of Pmcamentioning
confidence: 99%
“…The serendipitous discovery of an intronless gene for a human calmodulin-like protein [27] gained interest when it became clear that calmodulin-like protein (CLP) (human genome nomenclature CALML3) is a tumor-sensitive protein specifically expressed in normal epithelial cells but downregulated in tumorigenesis [29] . Dr. Strehler's group has characterized the biochemical properties of CLP [30,31] , provided the first description of the gene and its regulation [32] , and has shown that downregulation of the protein is an early event in breast cancer development [33] .…”
Section: Identification Of Human Calmodulin-like Protein (Calml3) As mentioning
confidence: 99%
“…The initial characterization of genomic DNA corresponding to the NB-1 transcript indicated the unexpected absence of introns. A literature search revealed the existence of a previously reported human calmodulin "pseudogene" hOH6, which shared identity with NB-1 cDNA (20). This gene was designated a pseudogene since the authors were unable to demonstrate the existence of a corresponding mRNA.…”
Section: Malignant Derivati:ves()f 184al and 184b5 Have Been Obtainmentioning
confidence: 99%